Linee per un’antropologia del corpo e dei sensi dell’attore teatrale: a partire da Helmuth Plessner (Itinera, 2013)
The essay on actor by Helmuth Plessner, linking anthropology and aesthetics, examines the functions of senses and body in the actor’s work, a question opened by the Eighteenth Century theatrical theories. An anthropological consideration of the actor reveals many relationships with the theory of images.